2015
DOI: 10.1590/s0100-736x2015000500015
|View full text |Cite
|
Sign up to set email alerts
|

Follicle and corpus luteum size and vascularity as predictors of fertility at the time of artificial insemination and embryo transfer in beef cattle

Abstract: Abstract:Two ultrasound based fertility prediction methods were tested prior to embryo transfer (ET) and artificial insemination (AI) in cattle. Female bovines were submitted to estrous synchronization prior to ET and AI. Animals were scanned immediately before ET and AI procedure to target follicle and corpus luteum (CL) size and vascularity. In addition, inseminated animals were also scanned eleven days after insemination to target CL size and vascularity. All data was compared with fertility by using gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
1
7
0
4
Order By: Relevance
“…Previous reports in other species have indicated that vascular development is essential for CL formation and maintenance, being luteal vascularization a requirement for an adequate P4 production and release into the general circulation (Balaro et al, ; Kanazawa et al, ). In fact, CL vascularization is associated with plasma P4 concentration and it has been proposed that it would be a good predictor of this hormone's concentration (cattle: Pinaffi et al, ; Kanazawa et al, ; Hassan et al, ; sheep: Figueira et al, ; goat: Balaro et al, ; horse: Ishak et al, ). In the present study, in both pregnant and non‐pregnant animals CL vascularization and P4 plasma concentration showed a similar profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports in other species have indicated that vascular development is essential for CL formation and maintenance, being luteal vascularization a requirement for an adequate P4 production and release into the general circulation (Balaro et al, ; Kanazawa et al, ). In fact, CL vascularization is associated with plasma P4 concentration and it has been proposed that it would be a good predictor of this hormone's concentration (cattle: Pinaffi et al, ; Kanazawa et al, ; Hassan et al, ; sheep: Figueira et al, ; goat: Balaro et al, ; horse: Ishak et al, ). In the present study, in both pregnant and non‐pregnant animals CL vascularization and P4 plasma concentration showed a similar profile.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular development is essential for CL formation and maintenance so the impairment of this process may lead to luteal insufficiency and affect pregnancy establishment (Chouhan et al, ). In fact, in different species CL vascularization is associated with plasma P4 concentration and so it has been proposed that luteal vascularization could be a good predictor of pregnancy rates (cattle: Acosta, Hayashi, Ohtani, & Miyamoto, ; Mann, ; Pinaffi et al, ; Kanazawa et al, ; sheep: Figueira et al, ; Arashiro et al, ; goat: Balaro, Santos, Moura, Fonseca, & Brandão, ; Cosentino et al, ; horse: Ginther, Gastal, Gastal, Utt, & Beg, ; Ishak, Bashir, Gastal, & Gastal, ). Similarly, in non‐pregnant llamas, plasma P4 and CL vascularization showed a similar profile after pharmacological induction of ovulation; suggesting an association between both variables (Ulloa‐Leal, Bogle, Adams, & Ratto, ).…”
Section: Introductionmentioning
confidence: 99%
“…A ultrassonografia modo Doppler colorido pode possuir diversas vantagens aplicáveis na rotina reprodutiva, entre elas a detecção da não gestação precoce e a seleção de fêmeas para programas de sincronização e ressincronização do estro e da ovulação (Pinaffi et al 2015). Essa ferramenta mostra a vascularização em um tecido, podendo ser utilizada com a finalidade de determinar o status fisiológico das estruturas ovarianas e uterinas (Herzog & Bollwein 2007).…”
Section: Introductionunclassified
“…O aumento do estradiol tem sido correlacionado também com alterações funcionais nos ovários referente ao maior aporte vascular, sendo fundamental para o suprimento adequado de metabólitos responsáveis pelo crescimento, maturação e ruptura folicular [2][3][4]39]. Seguindo essa linha de pesquisa, trabalhos com a ultrassonografia modo Doppler colorido, verificaram ainda que o incremento do fluxo sanguíneo folicular estava associado com uma maior produção de estradiol.…”
Section: Discussionunclassified